Distinct Localization of SNAP47 Protein in GABAergic and Glutamatergic Neurons in the Mouse and the Rat Hippocampus - Agnieszka Münster-Wandowski; Heike Heilmann; Felix Bolduan; Thorsten Trimbuch; Yuchio Yanagawa; Imre Vida; Imre Vida (Frontiers Media S.A., 2017)
Synaptosomal-associated protein of 47 kDa (SNAP47) isoform is an atypical member of the SNAP family, which does not contribute directly to exocytosis and synaptic vesicle (SV) recycling. Initial characterization of SNAP47 revealed a widespread expression in nervous tissue, but little is known about its cellular and subcellular localization in hippocampal neurons. Therefore, in the present study we applied multiple-immunofluorescence labeling, immuno-electron microscopy and in situ hybridization (ISH) and analyzed the localization of SNAP47 in pre- and postsynaptic compartments of glutamatergic and GABAergic neurons in the mouse and rat hippocampus. While the immunofluorescence signal for SNAP47 showed a widespread distribution in both mouse and rat, the labeling pattern was complementary in the two species: in the mouse the immunolabeling was higher over the CA3 stratum radiatum, oriens and cell body layer. In contrast, in the rat the labeling was stronger over the CA1 neuropil and in the CA3 stratum lucidum. Furthermore, in the mouse high somatic labeling for SNAP47 was observed in GABAergic interneurons (INs). On the contrary, in the rat, while most INs were positive, they blended in with the high neuropil labeling. ISH confirmed the high expression of SNAP47 RNA in INs in the mouse. Co-staining for SNAP47 and pre- and postsynaptic markers in the rat revealed a strong co-localization postsynaptically with PSD95 in dendritic spines of pyramidal cells and, to a lesser extent, presynaptically, with ZnT3 and vesicular glutamate transporter 1 (VGLUT1) in glutamatergic terminals such as mossy fiber (MF) boutons. Ultrastructural analysis confirmed the pre- and postsynaptic localization at glutamatergic synapses. Furthermore, in the mouse hippocampus SNAP47 was found to be localized at low levels to dendritic shafts and axon terminals of putative INs forming symmetric synapses, indicating that this protein could be trafficked to both post- and presynaptic sites in both major cell types. These results reveal divergent localization of SNAP47 protein in mouse and rat hippocampus indicating species- and cell type-specific differences. SNAP47 is likely to be involved in unique fusion machinery which is distinct from the one involved in presynaptic neurotransmitter release. Nonetheless, our data suggest that SNAP47 may be involved not only postsynaptic, but also in presynaptic function.